SICKLE KNIFE INJURY IN A 2-YEAR-OLD NON-DESCRIPT DOG: A CASE REPORT - D.T. Kaarthick; S. Vijayaboorani; D. Vishnugurubaran; K. Vijayakiran; A. Vijayarajan; E. Tamileniyan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A 2-year-old non-descript intact male dog was presented at Veterinary Clinical Complex, VCRI, Orathanadu, TANUVAS with a sickle cut wound on right forehead, right lateral part of shoulder and left lateral ofneck,with exposed tracheal rupture. As per the history the animal was attacked by a human using sickle knife. The defect was closed with appropriate techniques. After 14 days of post operative care the dog healed well and was back to normal routine.